2015
DOI: 10.1002/lary.25585
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes for chronic tracheostomy after chemoradiation for advanced laryngohypopharyngeal cancer

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
15
1
5
Order By: Relevance
“…Moreover, it has been proposed that tracheostomy is an adverse prognostic factor for the oncological outcome of patients with laryngeal cancer . However, this observation was not confirmed in cases of locoregionally advanced laryngeal cancers . Our study identifies locoregional relapse as an adverse factor for chronic tracheostomy dependency in patients undergoing tracheostomy for the initial treatment.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, it has been proposed that tracheostomy is an adverse prognostic factor for the oncological outcome of patients with laryngeal cancer . However, this observation was not confirmed in cases of locoregionally advanced laryngeal cancers . Our study identifies locoregional relapse as an adverse factor for chronic tracheostomy dependency in patients undergoing tracheostomy for the initial treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…The only surrogate factor regarding the primary tumor characteristics was a higher decannulation rate for supraglottic tumors. Similarly, a recent study by Jefferson et al (2015) identified subglottic extension as a risk factor for chronic tracheostomy dependency. However, they analyzed laryngeal and hypopharyngeal tumors together in a cohort of patients exclusively treated by CRT.…”
Section: Discussionmentioning
confidence: 84%
“…Tracheostomy rates in this review ranged from 0% to 6%. Small studies looking at tracheostomy in patients treated with chemoradiation ranged between 36% and 57% …”
Section: Discussionmentioning
confidence: 99%
“…Trakeostominin avantajlı yönleri arasında, trakeanın temizlenmesinin kolaylaşması ve trakeal yolla ilaç tatbiki mümkün olması da sayılabilmektedir. 10,47,48 Trakeostomili hastada aspirasyon yaşamsal öneme sahiptir. Uzamış trakeostomide ise hem motor nöronlar ve bunların nükleusundaki davranış değişiklikleri hem de kasların tonuslerini kaybetmelerinden dolayı dekanülasyon döneminde aspirasyon ve solunum sıkıntısı gibi durumlar ortaya çıkabil-mektedir.…”
Section: Trakeostomi̇ Bakimiunclassified
“…Bununla birlikte, aspirasyonda asepsinin önemi ve kanül çevresinin temizliği hakkında bilgilendirilmesi gerekmektedir. 10,47,48 AĞIZ KURULUĞU YÖNETİMİ Baş-boyun kanserlerinde radyoterapi sıklıkla tedavi hacmindeki tükürük bezlerini içermekte; tükürük bezlerine verilen hasar, tükürük akışını önemli derecede azaltmaktadır. Bu duruma ağız kuruluğu ve mukozitler de sıklıkla eşlik edebilmektedir.…”
Section: Trakeostomi̇ Bakimiunclassified